2011
DOI: 10.1021/mp200018y
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of cRGD Peptide to Chlorophyll a Based Photosensitizer (HPPH) Alters Its Pharmacokinetics with Enhanced Tumor-Imaging and Photosensitizing (PDT) Efficacy

Abstract: The αvβ3 integrin receptor plays an important role in human metastasis and tumor-induced angiogenesis. Cyclic Arg-Gly-Asp (cRGD) peptide represents a selective αvβ3 integrin ligand that has been extensively used for research, therapy, and diagnosis of neoangiogenesis. For developing photosensitizers with enhanced PDT efficacy, we here report the synthesis of a series of bifunctional agents in which the 3-(1′-hexyloxyethyl)-3-devinylpyropheophorbide-a (HPPH), a chlorophyll-based photosensitizer was conjugated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…19 Recent uorescence imaging studies with HPPH-CD aimed at tumor imaging also revealed the conjugate to have signicant tumor-imaging capability with excitation of the uorescent cyanine dye moiety in subcutaneous models created by the implantation of carcinoma cells such as RIF cells, colon 26 cells and human U87 cells. 27,28 Herein, our data paralleled previously published study that HPPH-CD showed great imaging efficacy in subcutaneous tumors using the S180 tumor model with obvious contrast between the tumors and surrounding tissues.…”
Section: Discussionsupporting
confidence: 86%
“…19 Recent uorescence imaging studies with HPPH-CD aimed at tumor imaging also revealed the conjugate to have signicant tumor-imaging capability with excitation of the uorescent cyanine dye moiety in subcutaneous models created by the implantation of carcinoma cells such as RIF cells, colon 26 cells and human U87 cells. 27,28 Herein, our data paralleled previously published study that HPPH-CD showed great imaging efficacy in subcutaneous tumors using the S180 tumor model with obvious contrast between the tumors and surrounding tissues.…”
Section: Discussionsupporting
confidence: 86%
“…10 Recently, the 14-mer bombesin, which is a high-affinity ligand for gastrin-releasing peptide receptor, was conjugated to a photosensitizer for use in PDT. 8 CTPs are more cost-effective ligands than antibodies, and it is relatively easy to prepare uniform conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that peptides with a RGD motif bind selectively to the a v b 3 integrin and cRGD (cyclic Arg-Gly-Asp) peptides were particularly useful for tumor targeting with therapeutics and imaging agents. Srivatsan et al conjugated the chlorophyll a derivative 2-(10-hexyloxyethyl)-2-devinylpyropheophorbide a (HPPH) to cRGD and confirmed specific targeting of a v b 3 integrin overexpressing tumors with the conjugated HPPH [98]. In vitro studies with 4T1 mouse mammary tumor and U87 human glioblastoma cells, both overexpressing the a v b 3 integrin, showed much higher phototoxicity of the conjugate in comparison to HPPH while in the a v b 3 -negative A431 cells the unconjugated HPPH was more phototoxic.…”
Section: Photosensitizers Conjugated To Peptidesmentioning
confidence: 98%